2018
DOI: 10.5114/reum.2018.80712
|View full text |Cite
|
Sign up to set email alerts
|

The importance of ultrasound examination in early arthritis

Abstract: ObjectivesTo assess the importance of ultrasound (US) examination of joints in hands and feet in patients with early arthritis and perform comparative analysis of the diagnostic value of US examination for 8, 12 and 52 selected joints.Material and methods123 patients (87 women, 36 men) with arthritis lasting less than 12 months, naive to disease-modifying anti-rheumatic drugs and glucocorticosteroids. Necessary differential diagnostics was performed for each patient. After the preliminary analysis, 72 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 24 publications
(19 reference statements)
0
15
0
Order By: Relevance
“…The Sum of PD grade correlated better with serum inflammatory markers (ESR and CRP) and assessments of patient global health (VAS-GH). All three previous studies that evaluated the correlations between MSUS parameters and clinical disease activity markers have shown that the sums of the PDUS or GSUS semi-quantitative grades correlated well with DAS28 in patients with established RA [ 33 , 42 , 43 ] and patients with EIA [ 19 ]. However, the sums of the GSUS grades did not exhibit significant correlations with DAS28, unlike the sums of the PDUS grades, in a study of 50 RA patients reported by El-Gohary et al [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sum of PD grade correlated better with serum inflammatory markers (ESR and CRP) and assessments of patient global health (VAS-GH). All three previous studies that evaluated the correlations between MSUS parameters and clinical disease activity markers have shown that the sums of the PDUS or GSUS semi-quantitative grades correlated well with DAS28 in patients with established RA [ 33 , 42 , 43 ] and patients with EIA [ 19 ]. However, the sums of the GSUS grades did not exhibit significant correlations with DAS28, unlike the sums of the PDUS grades, in a study of 50 RA patients reported by El-Gohary et al [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been many clinical studies using MSUS in assessing disease activity in patients with established RA [ 17 ]. MSUS studies scarcely evaluated disease activity in patients with early RA or UA that physicians could easily encounter in daily clinical practice [ 18 , 19 , 20 ]. Therefore, we focused on measuring the activity of synovitis in patients with EIA applying a pragmatic MSUS approach by limiting target joints only to those with arthritic signs.…”
Section: Introductionmentioning
confidence: 99%
“…Using the joint effusion index (JEI), synovial hypertrophy index (GSI) and power Doppler index (PDI) including 8 or 12 or 52 joints it is possible to predict occurrence of RA or remission of inflammation. The GSI assessment has especially prognostic value for UA patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography (US) versus magnetic resonance imaging (MRI) in joint evaluation in rheumatoid arthritis[24,25] InTable I the advantages and disadvantages of US vs MRI are presented.…”
mentioning
confidence: 99%
“…Ultrasound offers a clear advantage in assessing subclinical synovitis, which is important for the evaluation of radiographic progression risk and for the identification of patients who can maintain remission despite dose reduction [ 1 , 41 , 42 ]. Moreover, in ERA diagnosis, US allows for early detection of the disease and should be included in future classification criteria [ 43 45 ]. The application of a US is shown in Table I .…”
Section: Discussionmentioning
confidence: 99%